2014
DOI: 10.1080/19440049.2014.921936
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for the rapid detection of benzo(a)pyrene in liquid milk by dimethyl sulfoxide selectively enhanced synchronous fluorescence spectrometry

Abstract: Based on the high solubility efficiency and strong fluorescence response of benzo(a)pyrene (BaP) in dimethyl sulfoxide in combination with the high-performance derivative constant-energy synchronous fluorescence spectroscopic (DCESFS) technique, a simple, sensitive and economic method was developed for the determination of BaP in liquid milk. This method comprises ultrasound-assisted solvent extraction, solvent replacement and DCESFS detection. No saponification or other tedious clean-up procedures were needed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Synchronous fluorescence spectrometry (SFS) has been developed for the simultaneous analysis of multi‐component samples without pre‐separation. Studies have shown that SFS can avoid interference between different PAHs . Conventional SFS maintains a constant‐wavelength differential (Δλ) between excitation and emission monochromators, as each is scanned through the spectral region of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Synchronous fluorescence spectrometry (SFS) has been developed for the simultaneous analysis of multi‐component samples without pre‐separation. Studies have shown that SFS can avoid interference between different PAHs . Conventional SFS maintains a constant‐wavelength differential (Δλ) between excitation and emission monochromators, as each is scanned through the spectral region of interest.…”
Section: Introductionmentioning
confidence: 99%